Editorial - Capogna, Stefania; Minozzi, Manuela; Scarozza, Danila (Community Notebook. People, Education and Welfare in the Society 5.0, 2024)
This publication is part of the first intellectual output of the RE-EDUCO ERASMUS + project1 Rethinking EDUcation COmpetencies. Expertise, best practices, and teaching in Digital Era , an Erasmus+ - KA2 - Strategic Partnerships in the field of Education - project n. 2020-1-IT02-KA201-079433. RE-EDUCO was an action research project aimed at creating the optimum conditions for the exchange of best practices to produce innovation and cooperation in and between partner countries. RE-EDUCO encouraged the production, experimentation and exchange of new approaches and training methods in the field of digital culture, with the aim of widening the choices available to young people in their private and professional lives. Pondering both the dramatic labour supply-demand mismatch, which characterises in particular the world of professions and skills in digital fields and the increasing percentages of NEETs (Not in Education, Employment or Training) at risk of social exclusion and the complexification of transition paths during active life, the idea behind the project was to create spaces and opportunities for experimentation and virtuous collaboration to promote the establishment of an education chain understood as an integrated macro-system: education-training-university-orientation and transitions.